Effect of bottom electrodes on polarization switching and energy storage properties in Pb0.97La0.02(Zr0.95Ti0.05)O3 antiferroelectric thin films. (October 2015) - Fang, X.G.; Lin, S.X.; Zhang, A.H.; Lu, X.B.; Gao, X.S.; Zeng, M.; Liu, J.-M.
Abstract: Polarization switching and energy storage properties of a series of Pb0.97 La0.02 Zr0.95 Ti0.05 O3 (PLZT) thin films deposited on (100)-textured LaNiO3 (LNO)-buffered Si substrates and (111)-textured Pt/Ti/SiO2 /Si substrates were investigated. It was revealed that the PLZT films deposited on the (100)-textured LNO-buffered Si substrates prefer the (100) textured structure, while the orientation of the films deposited on the (111)-textured Pt-coated Si substrates is random. With respect to the films on the Pt-coated Si substrates, the (100) textured PLZT films have bigger compressive residual stress, larger electrical polarization, better dielectric properties, and better energy storage performances. For the (100)-orientated PLZT films, the energy density ( W s ) and efficiency ( η ) measured at room temperature are about 15.3 J/cm 3 and 56% respectively. Moreover, the better frequency stability in the range from 20 Hz to 10 kHz, and temperature stability in the range from 25 to 270 °C are demonstrated in the (100)-orientated PLZT films. These results indicate that the PLZT films with LNO bottom electrode could be potential candidate for applications in high energy storage density capacitors. Highlights: The (100) textured PLZT films are deposited on LNO buffered Si substrate. Ws of 15.3 J/cm 3 and h of 56% are obtained for (100) textured PLZT films. Frequency and temperature stabilities are presented for (100) textured PLZT films.